THE THEORY OF KNOWLEDGE ACCORDING TO BERTRAND RUSSELL - Asst. Lect. Hameed Abed Satar (Galaxy International Interdisciplinary Research Journal, 2024)
The 21st century witnesses rapid and significant changes in numerous components of life, necessitating a re-evaluation of the approach and pace of dealing with these modifications. This entails inspecting the vital branches and sections of philosophy as viewed by philosophers and thinkers of the beyond and attempting to benefit from their perspectives and numerous viewpoints on this area. The goal is for policymakers in education to satisfy these accelerating necessities and convince decision-makers to pick out the form of medical philosophy in curricula that aligns with the character of the curricula and research in the vicinity.